Quality of life in borderline patients comorbid with anxiety spectrum disorders - a cross-sectional study - Grambal, Ales; Prasko, Jan; Kamaradova, Dana; Latalova, Klara; Holubova, Michaela; Sedláčková, Zuzana; Hruby, Radovan (Patient preference and adherence, 2016)
INTRODUCTION: Borderline personality disorder (BPD) significantly reduces the quality of life (QoL) in mental, social, and work domains. Patients with BPD often suffer from depressive anxiety symptoms. The purpose of this cross-sectional study was to compare the QoL and demographic and clinical factors of inpatients diagnosed with BPD and comorbid anxiety spectrum disorders, and healthy controls. METHODS: Ninety-two hospitalized patients treated in the psychotherapeutic department and 40 healthy controls were included. Subjects were assessed by the Quality of Life Satisfaction and Enjoyment Questionnaire (Q-LES-Q), Dissociative Experiences Scale, Beck Depression Inventory (BDI)-II, Beck Anxiety Inventory, Clinical Global Impression, demographic questionnaire, Sheehan Disability Scale (SDS), and Sheehan Anxiety Scale. RESULTS: BPD patients suffered from comorbid anxiety disorders, panic disorder (18.5%), social phobia (20.7%), generalized anxiety disorder/mixed anxiety depression disorder (17.4%), adjustment disorder (22.8%), and posttraumatic stress disorder (8.7%); 19.6% patients had two or more anxiety disorder comorbidities. Patients score in Q-LES-Q (general) was 36.24±9.21, which was significantly lower in comparison to controls (57.83±10.21) and similar in all domains (physical health, feelings, work, household, school/study, leisure, social activities). The subjective level of depression measured by BDI and SDS (social life and family subscales) negatively correlated with all Q-LES-Q domains. CONCLUSION: Patients suffering from BPD and comorbid anxiety disorders have a lower level of QoL compared to healthy controls in all measured domains. Negative correlations of the Q-LES-Q domains with clinical scales (Dissociative Experiences Scale, BDI, Beck Anxiety Inventory, Sheehan Anxiety Scale, Clinical Global Impression, and SDS) are noticeable.
Keywords: borderline personality disorder; anxiety disorders; dissociation; quality of life; adjustment disorders